2017
DOI: 10.1521/aeap.2017.29.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Perception About HIV/AIDS, Self-Efficacy, and HIV Sexual Risk Behaviors Among Young Thai Men Who Have Sex With Men

Abstract: This study examined the relationships of HIV/AIDS beliefs, self-efficacy for AIDS preventive behaviors, perception of HIV as a chronic disease, and HIV risk behaviors among young Thai men who have sex with men. Participants were recruited for a self-administered anonymous survey through Facebook. Logistic regression analysis was used to identify factors associated with each of four HIV risk behavior outcomes. Factors associated with sexual risk behaviors included age (18 and 21 years), having a current regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 40 publications
3
23
1
7
Order By: Relevance
“…Our study also indicated that HIV testing self-efficacy was positively associated with lifetime HIV testing. This finding is consistent with previous studies, which have shown that improving HIV testing self-efficacy is useful for promoting HIV testing and medication adherence [ 18 20 ]. Our study suggests the importance of developing strategies (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also indicated that HIV testing self-efficacy was positively associated with lifetime HIV testing. This finding is consistent with previous studies, which have shown that improving HIV testing self-efficacy is useful for promoting HIV testing and medication adherence [ 18 20 ]. Our study suggests the importance of developing strategies (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…It could be argued that although there is evidence to suggest low perceived risk is associated with poor adherence in YMSM [61], this does not mean the opposite is necessarily true. It is important to point out that risk perception was part of a spectrum of other factors influencing risk taking behaviours not explicitly addressed by the intervention in this arm, such as addressing of barriers to condom use and alcohol use which may explain the outcomes observed in this study [62]. At the time of this study, there were no universally accepted validity tools available for the effectiveness of mobile applications prior to taking them to randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, belief factors have been verified as the crucial psychological factors associated with condom use behavior among MSM [ 8 , 9 ]. The psychological frame of the health belief model (HBM) has been proven associated with condom use behavior of anal sex among MSM in a previous qualitative study [ 10 ].…”
Section: Introductionmentioning
confidence: 99%